Study of The Proportion of Aloe Vera (Aloe vera L.) with Tomato (Lycopersicum esculentum Mill) and CMC Concentration on The Characteristics of Aloe Vera Jam - Dwiyan Audi Artantha; Lukman Hudi (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this research to identify the effect of aloe vera proportion with tomato and CMC concentration on the jam quality. This research used random group design (RAK). The first factor is treatment of the proportion of aloe vera with tomato consisting of 3 levels, there are LT1 (Alove vera 70%: tomato 30%), LT2 (Alove vera 67%: tomato 33%), and LT3 (Alove vera 30%: tomato 70%). Then, CMC concentration consisting of 3 levels, there are C1 (CMC 0,65%), C2 (CMC 0,75%) C3 (CMC 0,85%). The statistic analysis used analysis of variance (ANOVA) and further testing used BNJ test 5%. The result of this study indicated that there was no interaction between aloe vera proportion with tomato and CMC concentration toward all observation variable. However, treatment of aloe vera proportion with tomato have a signifcant effect on lightness value and yellowness value jam color test. Meanwhile, CMC concentration have not a significant effect toward all observation variable. The best calculation result is LT1C3 ( aloe vera proportion 70%: tomato 30% and CMC concentration 0,85%) which shows water level 17,88%, pH 4,33, Vitamin C 8,42, lightness value 26,96, redness value 1,80, yellowness value 3,96 and organoleptic color test 4,20 (rather like it), taste 5,00 (rather dislike-usual), aroma 3,80(rather dislike- usual), texture 4,13 (rather dislike-usual), topping power 3,97 (rather dislike-usual).